2007
DOI: 10.1007/s11481-007-9092-0
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Treatment is Associated with Increased Attentional Load-Dependent Brain Activation in HIV Patients

Abstract: Objective-The purpose of this paper was to determine whether antiretroviral medications, especially the nucleoside analogue reverse transcriptase inhibitors, lead to altered brain activation due to their potential neurotoxic effects in patients with human immunodeficiency virus (HIV) infection.Methods-Forty-two right-handed men were enrolled in three groups: seronegative controls (SN, n=18), HIV subjects treated with antiretroviral medications (HIV+ ARV, n=12), or not treated with antiretroviral medications (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
65
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 32 publications
(40 reference statements)
7
65
2
Order By: Relevance
“…Compared to low-risk individuals, high-risk individuals showed greater recruitment of a network of frontal lobe regions during performance on this task of inhibition. This greater recruitment of frontal brain regions in highrisk individuals is consistent with previous research suggesting the brain will attempt to maintain performance on cognitively demanding tasks by increasing activation in the compromised and adjacent brain regions (Chang, Yakupov, Nakama, Stokes, & Ernst, 2008;Drummond, Meloy, Yanagi, Orff, & Brown, 2005). Moreover, these results reflect the view in the current literature that neural vulnerabilities exist in at-risk individuals even prior to the initiation of substance use (Everitt et al, 2008;Wetherill et al, 2013).…”
Section: Introductionsupporting
confidence: 89%
“…Compared to low-risk individuals, high-risk individuals showed greater recruitment of a network of frontal lobe regions during performance on this task of inhibition. This greater recruitment of frontal brain regions in highrisk individuals is consistent with previous research suggesting the brain will attempt to maintain performance on cognitively demanding tasks by increasing activation in the compromised and adjacent brain regions (Chang, Yakupov, Nakama, Stokes, & Ernst, 2008;Drummond, Meloy, Yanagi, Orff, & Brown, 2005). Moreover, these results reflect the view in the current literature that neural vulnerabilities exist in at-risk individuals even prior to the initiation of substance use (Everitt et al, 2008;Wetherill et al, 2013).…”
Section: Introductionsupporting
confidence: 89%
“…Essentially, those patients with the strongest ERD had the lowest retention rates and those with the smallest ERD (or a slight ERS) had the highest retention rates, which makes sense given the pattern of strong ERS responses in uninfected controls. Previous parametric fMRI studies of working memory and attention have shown that uninfected controls exhibit stronger activation than patients in the right prefrontal cortices and the FEF during the easiest condition (e.g., lowest memory or attention load), but that this pattern reverses (patients>controls) as the memory load increases [13], [14]. Such observations are in line with the current findings and may suggest a failure to orient to the task, or more simply that the brain is less sensitive or less responsive to low-level stimulation that does not require extensive attentional resources.…”
Section: Discussionmentioning
confidence: 98%
“…More importantly, participants from our sample population were all newly diagnosed, just prior to the initiation of treatment. This would suggest that HIV could have a different impact on cortical function after treatment [46]. This will have to be confirmed with further prospective studies utilizing fMRI tasks that reliably engage the cortex and the striatum.…”
Section: Discussionmentioning
confidence: 95%
“…A possible explanation for why some studies found cortical dysfunction when we have not is that these studies differ from our present sample in terms of patient age and cART use. The additional effect of cART, as well as the effect of aging, has been associated with increases in cortical activation in HIV infection in their own right [46,47]. More importantly, participants from our sample population were all newly diagnosed, just prior to the initiation of treatment.…”
Section: Discussionmentioning
confidence: 99%